2010
DOI: 10.1016/j.schres.2010.03.043
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fallypride binding potential in patients with schizophrenia compared to healthy controls

Abstract: Background Molecular imaging of dopaminergic parameters has contributed to the dopamine hypothesis of schizophrenia, expanding our understanding of pathophysiology, clinical phenomenology and treatment. Our aim in this study was to compare 18F-fallypride binding potential BPND in a group of patients with schizophrenia-spectrum illness vs. controls, with a particular focus on the cortex and thalamus. Methods We acquired 18F-fallypride positron emission tomography images on 33 patients with schizophrenia spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…For the meta-analysis of thalamic D 2 /D 3 receptors some studies reported results of overlapping samples, in which case the study with the largest sample was selected for inclusion. Thus, Buchsbaum et al 33 was excluded as there was sample overlap with Lehrer et al 34 Also there was sample overlap between Yasuno et al, 35 Yasuno et al 36 and Suhara et al 37 Only Suhara et al 37 was included as the thalamic region used was closest to that of other studies in the available literature. For Talvik et al 38 and Talvik et al 39 there appeared to be sample overlap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the meta-analysis of thalamic D 2 /D 3 receptors some studies reported results of overlapping samples, in which case the study with the largest sample was selected for inclusion. Thus, Buchsbaum et al 33 was excluded as there was sample overlap with Lehrer et al 34 Also there was sample overlap between Yasuno et al, 35 Yasuno et al 36 and Suhara et al 37 Only Suhara et al 37 was included as the thalamic region used was closest to that of other studies in the available literature. For Talvik et al 38 and Talvik et al 39 there appeared to be sample overlap.…”
Section: Resultsmentioning
confidence: 99%
“…However, the random-effects approach to meta-analysis we used is relatively robust to heterogeneity. 34 Implications and future directions An updated version of the dopamine hypothesis proposes that negative and cognitive symptoms of schizophrenia are secondary to cortical hypodopaminergia, whereas psychotic symptoms are secondary to subcortical hyperdopaminergia. 7,8 In the past two decades consistent in vivo evidence has accrued for subcortical hyperdopaminergia, with a large effect size elevation in striatal dopamine synthesis and release in schizophrenia 9 and potentially sufficient specificity to be a biomarker.…”
Section: Studymentioning
confidence: 99%
“…Of the nine studies in thalamus (16, 8487, 9497), only one ((94), which overlaps with (98)) found lower D 2 in SZ, and meta-analysis (88) was negative. Likewise, no differences were found in globus pallidus (97), amygdala (16, 86, 87), entorhinal cortex (16, 86) or hippocampus (84, 86, 87).…”
Section: Imaging the Dopamine System In Schizophreniamentioning
confidence: 95%
“…Endophenotypic markers associated with dopaminergic function are an intriguing area for study. Analysis of existing PET data using high‐affinity dopamine receptor ligands, such as with 18F‐fallypride [Lehrer et al, ] or 11C‐FLB‐457 [Talvik et al, ] may indicate variations in binding anomalies or ligand distribution (cortical, thalamic, striatal) as a function of paternal age, possibly identifying pathophysiologic or neurodevelopmental aspects characteristic of illness related to paternal age. Analysis of large existing prepulse inhibition datasets [Swerdlow et al, ] with respect to paternal age could also clarify phenotypic features associated with this risk factor.…”
Section: Discussionmentioning
confidence: 99%